Effects of ambient temperature and injection pressure on biodiesel ignition delay - Jaat, Norrizam; Khalid, Amir; Andsaler, Adiba Rhaodah; Sapit, Azwan; Razali, Azahari; Basharie, Mariam (UMP Publisher, 2017)
Biodiesels are promoted as alternative fuels due to their potential to reduce dependency on fossil fuels. The main problem in diesel combustion chamber design is to understand the importance of interaction phenomenon between fuel spray and surrounding gas prior to ignition. Rapid compression machine (RCM) is widely used to acquire experimental insights into fuel autoignition at conditions relevant to the current and future combustion technologies. An experimental study of the measurement of ignition delay characteristics of diesel and blended biodiesel fuels in the RCM was carried out. The objective of this study is to investigate the effects of various ambient temperature, Ti and injection pressure, Pinj on ignition delay with different fuels used. This present study used the ignition delay of 5vol%, 10vol%, and 15vol% blending of palm oil methyl ester with a standard diesel as fuels in diesel engines called as B5, B10, and B15. The diesel fuel was blended with the biodiesel fuels at different fuel mixture blends. The injection pressure chosen was from 80 MPa to 140 MPa while an ambient temperature of RCM varied from 750 K to 950 K. The results showed that for all tested fuels, the reduction in ignition delay increased with the increase in ambient temperature and injection pressure. The palm oil biodiesel had higher density, viscosity, and cetane number, facilitated the shortest ignition delay when compared to the diesel fuel under all ambient temperatures and injection pressures. The fuel oxygen content in the biodiesel fuel also played a greater role in decreasing the ignition delay